Implementation of Medical Records in Physiotherapy Services Home Care in Semarang City - dani, Kuswar (Fakultas Syariah INSURI Ponorogo, 2024)
Many physiotherapists in the city of Semarang provide online health services and home care, By Minister of Health Regulation No. 269 and Law No. 36 of 2014 Article 56 (d), health workers are required to keep medical records. Medical records contain records of patient treatment, both written and recorded, which contain the patient's identity, history, laboratory, and diagnosis. This research aims to determine the implementation of medical records in physiotherapy services and home care in the city of Semarang, with analytical descriptive sociological juridical methods. In terms of how data collection is carried out by observation, interviews, questionnaires, documentation, and a combination of the four. The data results are analyzed systematically according to the factual and actual situation of the incident based on facts, characteristics, and phenomena by looking for cause and effect. The research results show the implementation of medical records in physiotherapy services and home care in the city of Semarang is not going well, because it is still found that 37.1% of physiotherapists have not carried out medical records. The physiotherapist can be given sanctions for violating UUPK number 29 of 2004 with a maximum penalty of 1 year and a fine of up to 50 million.